Capitalism : the reemergence of a historical concept - World Economic History Congress; Kocka, Jürgen 1941- HerausgeberIn; Linden, Marcel van der 1952- HerausgeberIn (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2016)
Machine generated contents note: -- Introduction (Jürgen Kocka, Social Science Research Center, Germany) -- 1. Economic and Financial Crises (Youssef Cassis, European University Institute, Italy) -- 2. Work and Labour Relations (Andrea Komlosy, University of Vienna, Austria) -- 3. The Crisis of Hyper-Consumerism: Capitalism's Latest Forward Lurch (Victoria de Grazia, Columbia University, USA) -- 4. Is There a Return of Capitalism in Business History? (Patrick Fridenson, Ecole des Hautes Etudes en Sciences Sociales, France) -- 5. Finance Capitalism (Harold James, Princeton University, USA) -- 6. Capitalism and Labour in Sub-Saharan Africa (Andreas Eckert, Humboldt University Berlin, Germany) -- 7. Capitalism as an Essential Concept to Understand Modernity (Immanuel Wallerstein, Yale University, USA) -- 8. The Return of Capitalism as a Concept (Gareth Austin, The Graduate Institute Geneva, Switzerland) -- 9. The New History of Capitalism (Sven Beckert, Harvard University, USA) -- Final Thoughts (Marcel van der Linden, International Institute for Social History, the Netherlands) -- Selected Bibliography -- Index